Sleep disorders in menopausal women - Singh, Abha; Daharwal, Abha; Kujur, Avinashi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Sleep disturbance is one of frequent sign and symptom encountered in post-menopausal women. It affects the quality of the life and may lead to depression in some women. Objective of present study was to find out the prevalence of sleep disorder in post-menopausal women Methods: Prospective study done on the post-menopausal women coming to Gynaecology OPD of Dr Bheem Rao Ambedkar Hospital, Raipur. This study was a prospective cross sectional observational study, conducted in the outpatient department of Obstetrics and Gynecology from 1st August 2016 to 31st January 2017. It included 500 women of postmenopausal age. A detail Performa was provided to assess sleep patterns and disorders associated with it. All the data was analysed using chi square test Results: The prevalence of sleep disturbances was 29.58%. Home makers were affected more in comparison to working women, 71,43% women had problems in initiating sleep. About 2/3rd women in the study group developed insomnia within 5 years of menopause, whereas 1/3rd took more than 7years to develop insomnia. Co morbidities were present in 48% women. Our women have mean age of menopause around 45 years. Conclusions: Sleep disorders are common, with prevalence of 29.5% in menopausal women in present study. It significantly causes psychosocial problems in women. There is need for it to be asked for and to be treated promptly.